2013
DOI: 10.1007/s00603-013-0413-8
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Mineralogy and Water Content on the Mechanical Properties of Argillite

Abstract: International audienceCallovo-Oxfordian (Cox) argillite was investigated in the context of feasibility studies for an underground repository for nuclear waste. In this study, the influence of mineralogical composition and water content on the mechanical properties of the Cox argillite was investigated. The samples were drilled from three representative depths at which the rock formations have different mineralogical compositions. Micro-indentation and mini-compression tests were performed on samples with diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Specimens with higher calcite content and smaller clay content extracted from layers deeper than that of the Bure URL are stiffer and stronger. 21 Ref. 7 also showed that the Young modulus increased with larger calcite content and decreased with larger clay fraction.…”
Section: Shear Strength and Thermal Effects In The Cox Claystonementioning
confidence: 84%
“…Specimens with higher calcite content and smaller clay content extracted from layers deeper than that of the Bure URL are stiffer and stronger. 21 Ref. 7 also showed that the Young modulus increased with larger calcite content and decreased with larger clay fraction.…”
Section: Shear Strength and Thermal Effects In The Cox Claystonementioning
confidence: 84%
“…Increase in porosity results in density decrease of a rock. Porosity depends on voids in the rock and is also affected by various processes during the rock formation and post-crystallization conditions (dissolution and recrystallization) (Tugrul, 2004;Molina et al, 2011;Hu et al, 2014).…”
Section: Implications Of Rock Textures To Rock Mechanicsmentioning
confidence: 99%
“…The results give the implications that the desaturation and resaturation would exert influences on its surroundings in the underground repositories. Hu et al [25] studied the anisotropic mechanical behavior, the Biot coefficient, and permeability coefficient caused by the development of microcrack tendency through complex cyclic loading and unloading tests on brittle rocks. Su et al [26] obtained the conclusion that during the triaxial cyclic loading and unloading test, the deformation of coal sample showed obvious memory characters, and the elastic modulus increased slightly with the increase of the cyclic series.…”
Section: Introductionmentioning
confidence: 99%